Insulin Treatment of Hypertriglyceridemia During Pregnancy - Cheng, De-cui; Su, Yao; Li, Feifei; Xu, Xianming (Frontiers in Pharmacology, 2022)
Abstract: Objective: This study aims to investigate the efficiency of insulin on the reduction of gestational lipid profiles and try to propose a real-world approach to assist clinicians. Methods: A retrospective, single centered cohort study of 35 cases was conducted from October 2018 to July 2021 in Shanghai General Hospital. SPSS version 25.0 was performed to analyze the whole data. For continuous variables, an independent t-test was carried out on each variable to make a comparison between before and after treatment. Results: The average pre-pregnancy TGs and TCs of these patients were about 3.96±1.42mmol/l and 4.78±1.18mmol/l separately . The maximum of TG before insulin treatment was up to 64.62mmol/l and TC 20.43mmol/L, which decreased to 17.34mmol/L and 4.92mmol/l after intervention of insulin drip. 77% was noticed to fall precipitously in terms of TG and 12.71% of TC. The difference of TG and TC between pre-therapy and post-treatment were statistically significant (p＜0.01）while this difference has not been found in the other laboratory tests reports. The outcomes of newborns and mothers management with insulin are proven to be well. Conclusion: The use of insulin in the managements of gestational hypertriglyceridemia is safe and efficient and insulin may become a mainstream in the near future to mitigate serum TG and TC levels in pregnancy period .